Ever-changing Big Science and Research Infrastructures: Evolving European Union policy - Inga Ulnicane (Edward Elgar Publishing, 2020)
This thought-provoking book expands on the notion that Big Science is not the only term to describe and investigate particularly large research projects, scientific collaborations and facilities. It investigates the significant overlap between Big Science and Research Infrastructures (RIs) in a European context since the early twenty-first century. Contributions to this innovative book not only augment the study of Big Science with new perspectives, but also launch the study of RIs as a promising new line of inquiry.